INNV-33. BARRIERS TO ACCRUAL AND ENROLLMENT IN BRAIN TUMOR TRIALS. (11th November 2019) - Lee, Eudocia; Chukwueke, Ugonma; Hervey-Jumper, Shawn; DeGroot, John; Leone, Pablo; Armstrong, Terri; Chang, Susan; Arons, David; Oliver, Kathy; Verble, Kay; Musella, Al; Willmarth, Nicole; et al.
Abstract: BACKGROUND: A major impediment to improving neuro-oncology outcomes is poor clinical trial accrual. METHODS: We convened a multi-stakeholder group including Society for Neuro-Oncology, Response Assessment in Neuro-Oncology, patient advocacy groups, clinical trial cooperative groups, and other partners to determine how we can improve trial accrual. RESULTS: We described selected factors contributing to poor trial accrual and possible solutions. We focused on patient and community factors, disparities, physician and provider factors, clinical trial factors, and site and organizational factors CONCLUSIONS: We will implement strategies with the intent to double accrual to neuro-oncology trials over the next 5 years.